Моделювання глибини розплавленого шару на поверхні напівпровідника за допомогою крос-платформного додатку JAVA - Галочкін, О.В.; Угрин, Д.І.; Ватаманіца, Е.В.; Солтис, І.В. (Vinnytsia National Technical University, 2022)
The paper describes a method for obtaining p-n transitions due to the laser recrystallization of the surface of CdTe semiconductor samples, as well as a software application developed in Java that allows the simulation of thermal processes at the boundary of the epitaxial layer-substrate with laser irradiation of the semiconductor surface. It allows to make predictions regarding the thickness of the melted layer, which will affect the parameters of the devices made on the basis of the obtained barrier layers. The theoretical modeling of the processes taking place at absorption of laser radiation by the surface layer of a semiconductor is carried out.